Theodor Karol Ballaban (1866–1946) – an ophthalmologist and a brygadier general of the Polish Army - Grzybowski, Andrzej; Kazało, Tomasz; Paluch, Mateusz; Rękas, Marek (Klinika Oczna / Acta Ophthalmologica Polonica, 2013)
Theodor Ballaban was born in 1866 and died in 1941. He was distinguished Polish ophthalmologist, a brigadier general with a degree of doctor of medical sciences obtained in Lviv, a social worker and the author of many works on ophthalmology. His son – Karol, who was an ophthalmologist, too, was murdered in Katyn in 1940. Theodor Ballaban described a medical case of central retinal vein occlusion, emphasizing that lack of spontaneous venous pulsation is a core sign of occlusion. Subsequent research confirmed this fact. The subjects of his other works were neuro-ophthalmology, ocular anatomy and ocular disease treatment methods.